2017
DOI: 10.1002/bit.26366
|View full text |Cite
|
Sign up to set email alerts
|

In vivo synergistic activity of a CAZyme cassette from Acidothermus cellulolyticus significantly improves the cellulolytic activity of the C. bescii exoproteome

Abstract: The use of microbial cells to convert plant biomass directly to fuels and chemicals is referred to as consolidated bioprocessing (CBP). Members of the bacterial genus, Caldicellulosiruptor (Gram-positive, anaerobic hyperthermophiles) are capable of deconstructing plant biomass without enzymatic or chemical pretreatment. This is accomplished by the production and secretion of free, multi-domain enzymes that outperform commercial enzyme cocktails on some substrates. Here, we show that the exoproteome of Caldicel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Initially, modular Caldicellulosiruptor β-glucosidases were introduced in H. thermocellum to relieve cellobiose inhibition of cellulases [103][104][105], and in turn, two different enzymes, a β-glucosidase from A. cellulolyticus [135] and cellobiose phosphorylase [136], were produced in C. bescii, which increased the efficiency of cellulose hydrolysis. An important first step in increasing cellulolytic activity in C. bescii was demonstrated by chromosomal expression of a β-glucanase and/or endoglucanse from A. cellulolyticus, which resulted in synergistic increases in cellulose hydrolysis, and over a 17-fold improvement of C. bescii growth on cellulose [137]. Heterologous expression of a cellobiose phosphorylase from Thermotoga maritima to relieve cellobiose inhibition improved the performance of the C. bescii endoglucanase knock-in strain [91], and the best gains in cellulolytic capacity were observed when all three enzymes (β-glucanase, endoglucanse, and cellobiose phosphorylase) were co-expressed in C. bescii [138].…”
Section: Heterologous Expression Of Cazymesmentioning
confidence: 99%
“…Initially, modular Caldicellulosiruptor β-glucosidases were introduced in H. thermocellum to relieve cellobiose inhibition of cellulases [103][104][105], and in turn, two different enzymes, a β-glucosidase from A. cellulolyticus [135] and cellobiose phosphorylase [136], were produced in C. bescii, which increased the efficiency of cellulose hydrolysis. An important first step in increasing cellulolytic activity in C. bescii was demonstrated by chromosomal expression of a β-glucanase and/or endoglucanse from A. cellulolyticus, which resulted in synergistic increases in cellulose hydrolysis, and over a 17-fold improvement of C. bescii growth on cellulose [137]. Heterologous expression of a cellobiose phosphorylase from Thermotoga maritima to relieve cellobiose inhibition improved the performance of the C. bescii endoglucanase knock-in strain [91], and the best gains in cellulolytic capacity were observed when all three enzymes (β-glucanase, endoglucanse, and cellobiose phosphorylase) were co-expressed in C. bescii [138].…”
Section: Heterologous Expression Of Cazymesmentioning
confidence: 99%
“…To refine the efficiency of Caldicellulosiruptor bescii as a plant degrader, CAZyme from Acidothermus cellulolyticus was introduced to act synergistically with the C. bescii exproteome. The study demonstrated that E1 endo-1,4-β- d -glucanase (GH5) of Acidothermus cellulolyticus acting in concert with CelA , increased the exproteome activity of Caldicellulosiruptor bescii on plant biomass [ 175 ].…”
Section: Microbial Strain Engineering Of Filamentous Fungi Yeast Andmentioning
confidence: 99%
“…Additionally, some of these enzymes show synergy with the more classical CAZymes with simpler architectures [ 7 ] in vitro and in vivo. For example, heterologous expression of the multifunctional GuxA (GH6/GH12) from A. cellulolyticus, in Caldicellulosiruptor bescii resulted in enhanced growth and cellulolytic activity of its exoproteome, but only in the presence of the endoglucanase, E1, from A. cellulolyticus [ 12 , 13 ]. E1 is a highly active and well characterized GH5 endoglucanase that was shown to exhibit high levels of synergy with several exoglucanases [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, heterologous expression of the multifunctional GuxA (GH6/GH12) from A. cellulolyticus, in Caldicellulosiruptor bescii resulted in enhanced growth and cellulolytic activity of its exoproteome, but only in the presence of the endoglucanase, E1, from A. cellulolyticus [ 12 , 13 ]. E1 is a highly active and well characterized GH5 endoglucanase that was shown to exhibit high levels of synergy with several exoglucanases [ 12 , 13 ]. GuxA on the other hand contains an N-terminal GH6 domain linked to a CBM3 followed by a GH12 catalytic domain linked to a CBM2 on the C-terminal end.…”
Section: Introductionmentioning
confidence: 99%